Pengaruh Konsumsi Kacang Ijo Terhadap Kejadian Anemia pada Ibu Hamil Di Puskesmas Sidorekso - Tri - Murtini; Indah Puspitasari; Dwi Astuti (Midwifery Care Journal, 2026)
Deficiency of several important nutrients, such as folic acid, iron, and vitamin B12, often leads to anemia in pregnant women. These nutrients are essential for the process of blood formation and maintaining the health of red blood cells. Pregnant women with anemia have a mortality risk up to 3.6 times higher than non-anemic pregnant women. Iron (Fe) deficiency, which is necessary for hemoglobin formation, is the primary cause of anemia among pregnant women in Indonesia. There are various ways to address and prevent anemia in pregnant women, including pharmacological methods such as administering iron supplements or oral iron tablets of 60 mg daily, and non-pharmacological methods such as consuming high-protein sources from both plant and animal origins. Mung beans are one of the richest legumes in iron.Based on the research results on the effect of green bean consumption on the incidence of anemia in pregnant women at Sidorekso Health Center, it was found that before the consumption of green beans and iron tablets, there were 11 respondents (73.3%) with mild anemia and 4 respondents (26.7%) with moderate anemia. After the consumption of green beans and iron tablets, there were 3 respondents (20.0%) with mild anemia and 12 respondents (80.0%) who were normal. The research results also show the distribution of anemia incidence in pregnant women at Sidorekso Health Center before the administration of iron tablets, where there were 6 respondents (40.0%) with mild anemia and 9 respondents (60.0%) with moderate anemia. Meanwhile, after the administration of iron tablets, there were 10 respondents (66.7%) with mild anemia and 5 respondents (33.3%) who were normal